2018
DOI: 10.1017/s1742170518000509
|View full text |Cite
|
Sign up to set email alerts
|

Investigating tarps to facilitate organic no-till cabbage production with high-residue cover crops

Abstract: High-residue cover crops can facilitate organic no-till vegetable production when cover crop biomass production is sufficient to suppress weeds (>8000 kg ha−1), and cash crop growth is not limited by soil temperature, nutrient availability, or cover crop regrowth. In cool climates, however, both cover crop biomass production and soil temperature can be limiting for organic no-till. In addition, successful termination of cover crops can be a challenge, particularly when cover crops are grown as mixtures. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Most importantly, roller-crimping is not as effective at fully terminating cover crops as flail mowing (Creamer and Dabney 2002) and therefore increases the risk of cover crop regrowth suppressing the cash crop. Plastic tarps placed over cover crops after roller-crimping can effectively terminate a rye–vetch cover crop and could eliminate this regrowth risk within vegetable systems (Lounsbury et al 2018) but are not practical in larger agronomic systems. The effectiveness of strip intercropping might also be enhanced through integration of a “cut and carry” system, in which residue is moved from the BR to the IR zone for suppression of IR weeds and to facilitate mechanical cultivation within the BR (Rostampour 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, roller-crimping is not as effective at fully terminating cover crops as flail mowing (Creamer and Dabney 2002) and therefore increases the risk of cover crop regrowth suppressing the cash crop. Plastic tarps placed over cover crops after roller-crimping can effectively terminate a rye–vetch cover crop and could eliminate this regrowth risk within vegetable systems (Lounsbury et al 2018) but are not practical in larger agronomic systems. The effectiveness of strip intercropping might also be enhanced through integration of a “cut and carry” system, in which residue is moved from the BR to the IR zone for suppression of IR weeds and to facilitate mechanical cultivation within the BR (Rostampour 2011).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent survey of organic growers in Michigan revealed that weed management was the most cited obstacle to adoption of RT, and these concerns were higher among vegetable growers compared to field crop growers (Lowry & Brainard, 2019b). Weed management challenges in organic RT vegetables have stimulated renewed interest in combining cover crop-based strategies with tarping (Lounsbury et al, 2018;Rylander et al, 2020aRylander et al, , 2020b, however these are currently more practical on a small scale (Fortier, 2014;Mefferd, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research comparing these practices over a wider range of soil, weather, and seedbank conditions could aid in the development of guidelines to help growers select practices that align with their situations and goals. We advocate as well that further studies follow Lounsbury et al [26] in examining the utility of solarization and tarping for terminating cover crops prior to organic no-till or strip-till plantings. Recent work on 'biosolarization' [57] and anaerobic soil disinfestation indicates that incorporation of crop residues [58] and other organic amendments [42,59] prior to treatment can increase the weed control efficacy of solarization and tarping.…”
Section: Comparing Solarization To Tarpingmentioning
confidence: 88%
“…However, in one study conducted during the fall in Israel, tarping outperformed solarization [25] perhaps because soil temperature during this relatively cool season was insufficient for weed control via solarization. In the Northeast USA, a single-year study found that tarping outperformed solarization as a method of cover crop termination [26], but we are aware of no prior studies comparing solarization and tarping for stale seedbed establishment in our region. The primary objective of this study was to test whether solarization combined with flaming could improve the efficacy of stale seedbed establishment in the Northeast USA.…”
Section: Introductionmentioning
confidence: 97%